PERAN TEKNOLOGI INFORMASI DAN KOMUNIKASI PADA PROGRAM KEMITRAAN PT TANIFUND MADANI INDONESIA (TANIFUND) - Kusnadi, Lydia Maria; Adi, Isbandi Rukminto (UI Scholars Hub, 2021)
The agricultural sector is one of the highest contributors to Indonesia’s GDP, even during the COVID-19 pandemic. The irony is that based on Indonesian Central Bureau of Statistics data, at least 25.14 million Indonesian were below the poverty line, with 15.15 million lives in rural areas and the majority of whom worked in the agricultural sector. TaniFund is a startup company with a vision to improve the welfare of farmers by utilizing information and communication technology (ICT). TaniFund builds partnerships with farmers in rural areas and opens access to capital through a peer-to-peer lending system. This study aims to describe the ICT in the TaniFund partnership program with farmers, using qualitative methods and a phenomenological approach through literature study, documentation, observation, and in-depth interviews. The results of the study identified the use of smartphones and internet access to support information and data exchange, communication applications, search engine sites, peer-to-peer lending systems, and long-distance remittances, as part of ICT. ICT plays a significant role as an enabler in this partnership, for TaniFund still uses several conventional approaches but it is ICT that allows the smoother, faster, more transparent, and accountable data and information exchange, also encouraging financial inclusion.